Analisis Struktur Ekonomi Dan Tantangan Pembangunan Indonesia Sebagai Negara Berkembang - Junaedi, Deddy; Maula, Hikmatul; Khdriah, Amelia Lailatul; Zahazvana, Alya Veronica (Jurnal Ekonomi dan Bisnis Digital, 2026)
Indonesia is a developing country with significant economic potential, supported by its large population, abundant natural resources, and strategic geographic position within the global economy. However, this potential has not yet fully enabled equitable distribution of prosperity and sustainable economic development. This study aims to analyze Indonesia's economic structure and the development challenges it faces as a developing country. The research method employed a descriptive qualitative approach through literature review. Data were obtained from publications by the Central Bureau of Statistics, reports from international institutions, development economics textbooks, and scientific journal articles. The analysis was conducted using a qualitative descriptive approach, linking development economics theory with the empirical conditions of the Indonesian economy. The results show that Indonesia's economic structure is still dominated by the primary sector, particularly agriculture, with a high proportion of workers in the informal sector. Despite a shift towards the industrial and service sectors, the role of the manufacturing industry in absorbing the formal workforce remains limited and uneven across regions.